Analysis of Syngas Combustion Process in Piston Engines - Mytrofanov O.; Proskurin A.; Kong W. (Problems of the Regional Energetics)
The article examines the features of the combustion process of hydrogen-containing gas (syn-gas) in the working cylinder of a spark-ignition internal combustion engine. The main objective of the study is to evaluate the heat release parameters of syngas. To achieve this goal, an exper-imental investigation was conducted to assess the nature of syngas combustion and establish its regularity. The most significant result is the derivation of dependencies for determining the cur-rent value of the combustion characteristic index m and the combustion duration φz in Professor I.I.Vibe's heat release model for spark-ignition engines operating on syngas, with an air excess ratio α ranging from 1.0 to 2.2 and hydrogen content in the fuel composition varying between 30% and 100% by volume. The significance of the obtained results lies in the establishment of the variability of the combustion index m (ranging from 1.6 to 5.5) in Professor I.I.Vibe's semi-empirical heat release model, which more closely corresponds to the actual heat release law ob-served in experimental studies. The proposed dependencies for determining m and φz allow for accounting the specific features of the syngas combustion process in spark-ignition engines, thereby significantly improving the accuracy of determining the indicated pressure in the work-ing cylinder (the relative root-mean-square error does not exceed 4.5%), which, in turn, enhanc-es the accuracy of assessing the engine's energy and economic parameters. The results of this study can be applied in the design and construction of new spark-ignition engines running on alternative fuel.